Ayurvedic management of cirrhotic ascites - G Aswathy; Prasanth Dharmarajan; Ananth Ram Sharma; V K Sasikumar; M R Vasudevan Nampoothiri (Ancient Science of Life, 2016)
Cirrhosis is the final stage of most of the chronic liver diseases and is most invariably complicated by portal hypertension resulting in ascites. A case of chronic liver disease with portal hypertension (cryptogenic cirrhosis), managed at Amrita School of Ayurveda is discussed in this paper. The clinical picture was that of an uncomplicated cirrhotic ascites. Snehapāna (therapeutic oral administration of lipids) followed by virecana (purgation) was done after an initial course of nityavirecana (daily purgation). Later Vardhamāna pippalī rasāyana [administration of single drug - pippalī (piper longum) in a structured dose pattern] was administered with an intention of rejuvenating liver cells. Ascites and lower limb oedema were completely resolved after the therapy. No recurrence of ascites has been reported after a follow up period of one year.